2017
DOI: 10.1111/jmwh.12624
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pessary Care: A Modified Delphi Consensus Study

Abstract: Expert pessary providers were able to develop consensus recommendations to inform provider education and clinical care where the evidence base remains sparse. Areas where consensus was not achieved inform the future pessary-related research agenda needed to identify optimal cost-effective pessary care and educational methods for new pessary providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Overall, consensus on the optimal interval is lacking. 17,21,22 Based on our results, practitioners can consider extending follow-up periods for pessary cleanings beyond 3 months without incurring increased risk of adverse outcomes in racially/ethnically diverse women. An extended interval may increase pessary acceptance given the convenience of fewer in-person office visits, including decreased transportation costs, less time off work, and reduced need for caregiver or family accompaniment.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Overall, consensus on the optimal interval is lacking. 17,21,22 Based on our results, practitioners can consider extending follow-up periods for pessary cleanings beyond 3 months without incurring increased risk of adverse outcomes in racially/ethnically diverse women. An extended interval may increase pessary acceptance given the convenience of fewer in-person office visits, including decreased transportation costs, less time off work, and reduced need for caregiver or family accompaniment.…”
Section: Discussionmentioning
confidence: 79%
“…17 The optimal duration between pessary maintenance visits to minimize risk of adverse events is unknown. 17,[21][22][23] The lack of consensus on pessary care posed a unique challenge in March 2020 when the coronavirus disease 2019 (COVID-19) pandemic unexpectedly mandated changes in standard clinical practice. New York City was declared the U.S. epicenter of the pandemic in March 2020.…”
mentioning
confidence: 99%
“…36 In a study of nurses who manage pessaries, there was 100% consensus for obtaining a PVR before and after fitting a pessary. 37 The reasoning is that although vaginal pessary is likely to resolve urinary retention by relieving a kinked urethra and restoring normal anatomy, that urethral obstruction can still occur; therefore, clinicians should assess the PVR after a pessary fitting in symptomatic or at-risk women.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that an interval of 3 months versus a 9-month interval did not influence the severity of pessary-related side effects. In the literature, it is often recommended to apply intervals of between 3 to 6 months [ 1 , 12 , 16 , 17 ]. However, we found no evidence to support these recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Equally important, we do not know whether these visits are effective in reducing pessary related side effects. Further, intervals between these follow-up visits vary widely and studies about the ideal length of such intervals are lacking [ 1 , 7 , 11 , 16 , 17 ]. Nor is it known what proportion of patients is willing and able to learn how to clean and replace the pessary themselves.…”
Section: Introductionmentioning
confidence: 99%